The Influence of Workload, Non-Physical Work Environment and Remuneration on the Performance of Lecturers - Alfa P Siwalette; Gerrit Pentury; Wylda Olivia Kowey (ProBisnis : Jurnal Manajemen, 2023)
The purpose of the research was to determine the effect of the variable workload, non-physical work environment and remuneration on performance. The sample in this research was 66 Lecturers of the Faculty of Agriculture, University of Pattimura Ambon, determining the number of samples using the slovin method with the Proportionate Stratified Random Sampling technique. Data collection was carried out by distributing questionnaires using a Likert scale. The analytical tool used in this research is SPSS 23. The results obtained from this research are: Workload Has no significant effect on lecturer performance, Non-Physical Work Environment has a significant effect on Lecturer Performance Remunerationsignificant effect on lecturer performance